FAKTOR-FAKTOR LINGKUNGAN RUMAH YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA : SEBUAH KAJIAN SISTEMATIS - Laliyanto; Nurjazuli Nurjazuli; Suhartono (Poltekkes Kemenkes Yogyakarta, 2022)
Pneumonia in children under five is still a world health problem, accounting for 14% of all deaths of children under five years of age and causing 740,180 deaths in children in 2019. Di Indonesia pneumonia is still the main problem that causes 14.5% of deaths in children aged 29 days - 11 months. The purpose of the study was to explain the impact and potential risks of the physical environment of the house, such as PM10, PM2.5, the presence of cigarettes in the house, ventilation area, floor type, wall type, ceiling presence, and humidity with the incidence of children under five years pneumonia. This research method uses a systematic review to summarize the results of previous studies. The results of the study from the 12 articles studied found that the physical environment of the house, including such as PM10 levels, PM2.5 levels, the presence of cigarettes in the house, qualified ventilation area, wall type, ceiling, and humidity are risk factors for toddler pneumonia. Floor-type variables were not significantly correlated with pneumonia in children under five years.